“Terrific weight of rock above me”: Alan Caswell Collier’s Mining Art - Neary, Peter (Ontario History, 2022)
Alan Caswell Collier (1911-1990) was a major Ontario landscape artist of the twentieth century and, in the 1940s and 1950s, advanced his career through depictions of mines and miners, having himself worked underground in Northern Ontario during the Great Depression. His 1968 commissioned picture, Mining in Ontario, is now part of the art collection at the Macdonald Block, Queen’s Park. Collier’s voluminous papers are in the archives of Queen’s University and this paper is based on extensive research in this collection, a major source for scholars of Ontario’s art history. Mining was a leading industrial activity in the province in the twentieth century, and Collier was at the fore in representing its development artistically. He was at once an uncommon but ordinary Ontarian – uncommon in his talent but in many other respects an Anglo-Canadian everyman: he lived in relief camps and bunkhouses in the 1930s, served in uniform in the 1940s, and moved to Toronto suburbia in the 1950s. His mining art recalls an expansive boom period in the history of Ontario industry.